Fluorescently Labeled α-Conotoxin TxID, a New Probe for α3β4 Neuronal Nicotinic Acetylcholine Receptors - Meiling Huang; Xiaopeng Zhu; Yishuai Yang; Yao Tan; Sulan Luo; Dongting Zhangsun (Marine Drugs, 2022)
Neuronal nicotinic acetylcholine receptors (nAChRs) are important ion channel membrane proteins that are widely distributed in the central nervous system (CNS) and peripheral nervous system (PNS). As an important member, α3β4 nAChRs are related to pain sensation in PNS and nicotine addiction in CNS. However, research related to the α3β4 nAChRs is greatly limited by the lack of subtype-selective pharmacological tools. The α-conotoxin (α-CTx) TxID from the marine cone snail, Conus textile, is a selective α3β4 nAChR antagonist with relatively high potency. In this study, a fluorescent dye (5-TAMRA SE) was used to label TxID on the N-terminus of α-CTx TxID, and pure TxID-F (fluorescent analogue of TxID) was obtained by HPLC. At the same time, the potency and selectivity of TxID-F were detected by high-performance liquid chromatography (HPLC). Additionally, the potency and selectivity of TxID-F were determined by using a two-electrode voltage-clamp technique on various nAChRs expressed in the Xenopus oocyte expression system. The results obtained by electrophysiology showed that TxID-F maintained the same order of potency (IC50 73 nM) as the native toxin (IC50 25 nM) for the α3β4 nAChR subtype. In addition, the results of fluorescent spectroscopy and circular dichroism showed TxID-F has the same fluorescence as 5-TAMRA SE, as well as similar profiles as TxID. The results of flow cytometry showed that the histogram shifted significantly to the right for the RAW264.7 cells expressing α3β4-containing nAChRs stained with TxID-F and confirmed by live cell imaging. The study of fluorescent-labeled α-CTx TxID provides a rich pharmacological tool to explore the structure–function relationship, distribution, and ligand-binding domain of α3β4 nAChR subtype in the future.